ANALISIS PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, KOMISARIS INDEPENDEN DAN KONSENTRASI KEPEMILIKAN TERHADAP INTELLECTUAL CAPITAL DISCLOSURE (Students' Journal of Accounting and Banking, 2014)
Intellectual capital has a very important role in enterprise and strategic. Intellectual capital represents a valuable resource and the ability to act based on knowledge. This study aims to examine and analyze the effect of firm size, firm age, independent commissioner and the concentration of ownership of the intellectual capital disclosure. The population in this study are all companies listed on the Indonesia Stock Exchange in 2012. Sampling technique is purposive sampling. Based on purposive sampling obtained a sample of 68 companies. The data analysis technique used is multiple linear regression analysis. Based on the test results it can be concluded that the positive effect of firm size on the disclosure of intellectual capital. The larger the company the greater the attention of stakeholders as social and economic impact to the environment. Therefore, more and more companies are required to report information including disclosure of intellectual capital. Other independent variables such as age of the firm, an independent commissioner and ownership concentration proved statistically no significant effect on intellectual capital disclosures. Keywords: firm size, firm age, independent commissioner, the concentration of ownership and intellectual capital disclosure